Proceedings of the 33rd Annual ACM Symposium on User Interface Software and Technology 2020
DOI: 10.1145/3379337.3415876
|View full text |Cite
|
Sign up to set email alerts
|

DefeXtiles

Abstract: Figure 1: Length scale overview of DefeXtiles from millimeters to decameters. (1) microscope image of a DefeXtile being printed, (2) A DefeXtile being stretched, (3) an interactive lampshade with capacitive sensing, (4) a full-sized skirt, (5) a 70m roll of fabric produced in a single print. All samples were printed on a desktop FDM printer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…In the realm of woven structures, Partsch et al [119] focused on three-dimensional printing of fabrics with various woven configurations, yarn cross-sections and yarn densities. More recently, novel strategies for printed woven and quasi-woven flexible textiles have been proposed in [120,121]. Flexible three-dimensionally-printed garments can also be designed using non-conventional textile structures.…”
Section: Mathematics Of Digital Manufacturing and Smart Textilesmentioning
confidence: 99%
“…In the realm of woven structures, Partsch et al [119] focused on three-dimensional printing of fabrics with various woven configurations, yarn cross-sections and yarn densities. More recently, novel strategies for printed woven and quasi-woven flexible textiles have been proposed in [120,121]. Flexible three-dimensionally-printed garments can also be designed using non-conventional textile structures.…”
Section: Mathematics Of Digital Manufacturing and Smart Textilesmentioning
confidence: 99%
“…Besides fashion applications, the design space of 3DP textiles has been explored to produce knit-like [29][30][31] and biaxial weave structures [32][33][34] using powder bed fusion (PBF) and material extrusion (MEX) techniques respectively. Further research has expanded traditional textile geometries by creating mesh-like structures [35,36], kinematic structures [37,38], textile substrate printing [39][40][41], and woven lattice structures [42].…”
Section: Introductionmentioning
confidence: 99%
“…It should be also stated that new approaches have been presented to produce textile-like structures in FDM technology. Forman et al (2020) presented the method called defeXtiles – quasi-woven fabric structures – that enables the production of flexible fabric-like structures produced in FDM technology with nonflexible materials. Later, Dorsey et al (2022) revealed the effects of printing parameters on the mechanical properties of 3D-printed parts for defeXtiles method.…”
Section: Introductionmentioning
confidence: 99%